2010
DOI: 10.1352/1944-7558-115.6.504
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Novel Community-Based Early Intervention Model for Children With Autistic Spectrum Disorder

Abstract: The Nova Scotia early intensive behavior intervention model -NS EIBI ( Bryson et al., 2007 ) for children with autistic spectrum disorders was designed to be feasible and sustainable in community settings. It combines parent training and naturalistic one-to-one behavior intervention employing Pivotal Response Treatment - PRT (R. Koegel & Koegel, 2006 ). We followed 45 children (33 males, mean baseline age  =  50 months) for 12months. Mean gains of 14.9 and 19.5 months were observed on expressive and receptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 46 publications
(79 reference statements)
2
42
0
2
Order By: Relevance
“…1 Earlier diagnosis would alleviate prolonged concerns of many families and expedite opportunities to benefit from specialized interventions, 37,38 thereby reducing costs to families and society. 39 Parental reports, analyses of home videos and, more recently, prospective studies of infants at increased risk of ASD have identified numerous red flags that distinguish toddlers with ASD from those with typical development or other developmental delays (Box 4).…”
Section: How Can We Detect Asd Early?mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Earlier diagnosis would alleviate prolonged concerns of many families and expedite opportunities to benefit from specialized interventions, 37,38 thereby reducing costs to families and society. 39 Parental reports, analyses of home videos and, more recently, prospective studies of infants at increased risk of ASD have identified numerous red flags that distinguish toddlers with ASD from those with typical development or other developmental delays (Box 4).…”
Section: How Can We Detect Asd Early?mentioning
confidence: 99%
“…68 A key question is whether effective high-quality programs can be less costly and more sustainable; the findings from Nova Scotia are promising. 38 Studies of the effectiveness of treatment programs for older children, youth and adults with ASD are scarce. Benefits have been reported for structured teaching practices, including ABAbased interventions, for a wide range of skill deficits and maladaptive behaviours.…”
Section: Behavioural Interventionsmentioning
confidence: 99%
“…Algunos se centran en la eficacia de programas concretos (Dawson et al, 2010;Lydon, Healy y Leader, 2011;Peters-Scheffer, Didden, Mulders y Korzilius, 2010;Roberts et al, 2011;Smith et al, 2010) y otros son revisiones sistemáticas (Magiati, Moss, Charman y Howlin, 2011;Makrygianni y Reed, 2010;Odom et al, 2010;Peters-Scheffer, Didden, Korzilius y Sturmey, 2011;Virués-Ortega, 2010;Warren et al, 2011a). Las conclusiones que se pueden obtener a partir de la revisión de la literatura actual apoyan la idea, ya aportada por estudios realizados hace más de una década, de que los programas que se basan en el análisis conductual aplicado, y especialmente los que son más intensivos, obtienen algunos resultados positivos en las áreas de habilidades cognitivas, comunicación y conducta adaptativa.…”
Section: Los Programas Integrales De Atención Tempranaunclassified
“…This has allowed for collaborative treatment and opportunities to teach skills within the context of children's daily routines (Smith et al 2010). This approach, known as family centered intervention, has also been demonstrated to lead to positive outcomes for ASD (Smith et al 2010).…”
Section: Overview Of Current Treatmentmentioning
confidence: 99%
“…This approach, known as family centered intervention, has also been demonstrated to lead to positive outcomes for ASD (Smith et al 2010). Intensive community based interventions based on PBS and positive support strategies have yielded positive outcomes with respect to enhanced language and communication as well as reductions in problem behavior (Perry et al 2008;Smith et al 2010).…”
Section: Overview Of Current Treatmentmentioning
confidence: 99%